Bunt młodych w XIX-wiecznym Wilnie. Fragment z dziejów Towarzystwa Filomatów - Klimus, Elżbieta (Przegląd Wschodnioeuropejski, 2024)
Teenage rebellion is a part of social development in adolescents in order for them to develop an identity independent from their parents or guardians. Moreover, teens shape identity through revolt. This phenomenon affected also members of the Philomath Society, which was formed in 1817 at the Imperial University of Vilnius. Philomaths rebelled against the old generation, upbringing methods, weakness in the Society, idleness of youth. They were not indifferent to the political situation, so that they mutinied against the Russian Empired. The Philomath Society’s rebellion manifested in rule of the secrecy, pedagogic activity (formation of the youth associations, work as teachers), prosocial activity, language and tradition preserving. Teenage rebellion of Philomaths aimed at changing the reality, which was unacceptable.